Archaeomagnetic evidence indicates post-Inka reheating of metallurgical kilns at Quillay (NW Argentina) - Judit del Río; Miriam Gómez-Paccard; Alicia Palencia-Ortas; Annick Chauvin; Mara Basile; Norma Ratto; Pablo Cruz; Marco Antonio Giovannetti (PLoS ONE, 2026)
This study presents an archaeomagnetic analysis of five metallurgical kilns from the settlement of Quillay (Catamarca, NW Argentina), attributed to the Inka period on the basis of radiocarbon dates and archaeological evidence. All five structures yielded consistent paleofield values, and directional and intensity determinations are statistically indistinguishable which suggests that the sampled parts of the kilns were reheated within a relatively short interval. Comparison with geomagnetic field models, particularly BIGMUDI4k.1, indicates that this last heating event occurred between the late nineteenth and mid-twentieth centuries, rather than during the Inka occupation. The discrepancy between the archaeomagnetic and radiocarbon evidence is therefore consistent with a later remagnetization event affecting the structures. Possible explanations include a local wildfire or the deliberate re-use of the upper chambers to recover copper from slag. The results refine our knowledge about the occupational history of Quillay, and support the interpretation of a later thermal event affecting structures originally used in Inka times.